Evaluation of Microbial Contamination of Combs and Brushes in Beauty Salons within the University of Port Harcourt, Rivers State, Nigeria - , H. O. Stanley; , T. T. Oba; , C. J. Ugboma (Archives of Current Research International, 2019)
Beauty salons may provide a suitable medium for the growth and transfer of pathogenic microorganisms which may be of public health significance. This study was aimed at investigating the microbial contamination of beauty salon tools within the University of Port Harcourt, Rivers State, Nigeria. Nutrient agar was used for the determination of total culturable heterotrophic bacterial counts and Potato dextrose agar was used for the determination of total spore counts. Bacterial isolates were subjected to different biochemical tests while the fungal cultures were identified by macroscopy and microscopy. Results revealed bacterial load obtained from combs and brushes across the three campuses studied ranged from 6.3x105 to 2.8x106 CFU/swab area and 5.8x105 to 1.8x106 CFU/swab area respectively. Total spore counts obtained from combs and brushes across the three campuses ranged from1.8x105 to 1.0x106 CFU/swab area and 4.2x105 to 9.3x105CFU/swab area respectively. The bacterial isolates obtained from the salon tools include Staphylococcus aureus, Bacillus spp., Micrococcus spp.,Serratia spp.,Citrobacter spp., Proteus spp. and Shigella spp., while the fungal isolates include Aspergillus flavus, Penicillium spp., Tricophyton spp. and Microsporium spp. Staphylococcus aureus (27.7%) and Bacillus spp.(22.2%) were the predominant bacterial isolates in the study while Aspergillus flavus (36.3%) and Penicillium spp.(27.3%) were the most occurring fungi. The study showed that fomites used in beauty salons harbour significantly high microbial load including microorganisms of possible public health significance.